2019
DOI: 10.1017/s0030605318001588
|View full text |Cite
|
Sign up to set email alerts
|

Potential ecological and socio-economic effects of a novel megaherbivore introduction: the hippopotamus in Colombia

Abstract: Introduced species can have strong ecological, social and economic effects on their non-native environment. Introductions of megafaunal species are rare and may contribute to rewilding efforts, but they may also have pronounced socio-ecological effects because of their scale of influence. A recent introduction of the hippopotamus Hippopotamus amphibius into Colombia is a novel introduction of a megaherbivore onto a new continent, and raises questions about the future dynamics of the socio-ecological system int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
0
16
1
5
Order By: Relevance
“…By managing to survive and reproduce without human assistance, these mammals have become an invasive species. Fecundity is a known trait in hippos: females can start having offspring at three years of age, and can bear a calf every two or three years for up to four decades (Subalusky et al, 2021)! Although the original group came from the United States, hippos are African herbivores that are still found, in declining numbers, in various spots across West, Central, and East Africa.…”
Section: Invaders and Refugeesmentioning
confidence: 99%
See 1 more Smart Citation
“…By managing to survive and reproduce without human assistance, these mammals have become an invasive species. Fecundity is a known trait in hippos: females can start having offspring at three years of age, and can bear a calf every two or three years for up to four decades (Subalusky et al, 2021)! Although the original group came from the United States, hippos are African herbivores that are still found, in declining numbers, in various spots across West, Central, and East Africa.…”
Section: Invaders and Refugeesmentioning
confidence: 99%
“…Three more male hippos have been castrated, but the herd continues to grow, and occasionally scare and injure neighbors (Suárez, 15 Mar. 2011;Subalusky et al, 2021). Like Escobar's, the hippos' fame goes well beyond Colombia; they appear in YouTube videos, have starred in several documentaries, and are the subject of scholarly articles (Pablo's..., 2009(Pablo's..., , 2012Los hipopótamos..., 2011).…”
Section: Invaders and Refugeesmentioning
confidence: 99%
“…Following Escobar's fall, hippos escaped confinement and invaded floodplains in the Middle Magdalena River basin. Ample suitable habitat and the absence of natural enemies have allowed the hippos to proliferate, which are now having overt impacts on social and ecological systems throughout the region (Subalusky et al 2019;Shurin et al 2020).…”
mentioning
confidence: 99%
“…Environmental agencies attempts to control their reproduction have had no impact on population growth, and nowadays an estimate of between 93 and 102 hippos inhabit an area of around 2,000 square kilometers (Castelblanco-Martínez et al 2021). Empirical evidence has demonstrated that hippos are important drivers of habitat modification, being capable to dramatically change the chemical and structural features of aquatic and terrestrial ecosystems (Stears et al 2018;Subalusky et al 2019). In the long term, this may pose an important risk to many native species and environmental services.…”
mentioning
confidence: 99%
“…In the last years, several research teams have addressed this case from the ecological point of view (e.g. Castelblanco-Martínez et al 2021;Shurin et al 2020;Subalusky et al 2019), providing necessary input for the debate. However, we need a transdisciplinary approach to solve the dilemma related to the management of this non-native species in Colombia.…”
mentioning
confidence: 99%